The impact of the European Union on Turkish counter-terrorism policy towards the Kurdistan Workers Party - Ilbiz, Ethem (2014)
This study seeks to examine the impact of the EU on Turkish counter-terrorism policies towards the Kurdistan Workers Party (PKK). It analyses what impact it has had within three distinct periods: the pre-Helsinki European Council (1984-1999) period, the post-Helsinki European Council (1999-2004) period, and the post-Brussels European Council (2004-2013) period. It conceptualizes and empirically investigates the EU’s norm diffusion role by relying on the concept of “Rule Adoption”, and by utilising two norm diffusion mechanisms: the “Conditionality” and the “Socialization” mechanism, and their domestic and EU-level determinants. The thesis argues that when the EU has promoted democratisation in Turkey, it has also implicitly impacted on Turkey’s counter-terrorism policies. It argues for this thesis by generalizing from the following empirical findings: When the EU has provided a credible membership prospect to Turkey, and when the PKK attacks have been at a low-level, then the EU conditionality mechanism has been influential on Turkey’s adoption of EU promoted norms. However, when there has been no membership prospect and high levels of PKK violence, it has been the openness of Turkish political actors that has resulted in rule adoption, in which the social learning of the Turkish political actors has led to the adoption of EU promoted norms as an appropriate way to solve existing terrorism problems.